2016
DOI: 10.1038/srep19134
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation dynamics in mouse preimplantation embryos revealed by mass spectrometry

Abstract: Following fertilization in mammals, paternal genomic 5-methyl-2′-deoxycytidine (5 mC) content is thought to decrease via oxidation to 5-hydroxymethyl-2′-deoxycytidine (5 hmC). This reciprocal model of demethylation and hydroxymethylation is inferred from indirect, non-quantitative methods. We here report direct quantification of genomic 5 mC and 5 hmC in mouse embryos by small scale liquid chromatographic tandem mass spectrometry (SMM). Profiles of absolute 5 mC levels in embryos produced by in vitro fertiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 56 publications
1
37
1
3
Order By: Relevance
“…In summary, GO term analysis offered no striking outliers in functional categories within our screen results and suggests that preimplantation development equally requires all aspects of cellular and molecular function for success. Supporting this notion, previous studies have found essential roles during preimplantation for genes within each of these functional categories (including DNA/RNA/protein binding4546, catalytic activity4748, various transporter activity495051). …”
Section: Resultsmentioning
confidence: 71%
“…In summary, GO term analysis offered no striking outliers in functional categories within our screen results and suggests that preimplantation development equally requires all aspects of cellular and molecular function for success. Supporting this notion, previous studies have found essential roles during preimplantation for genes within each of these functional categories (including DNA/RNA/protein binding4546, catalytic activity4748, various transporter activity495051). …”
Section: Resultsmentioning
confidence: 71%
“…For example, 5′ long terminal repeat-containing element is demethylated after fertilization (Smith et al 2014). As embryos develop to the blastocyst stage, repression is slowly reversed in the inner cell mass, and methylation status becomes increased (Smith et al 2012, Guo et al 2014, Okamoto et al 2016.…”
Section: Epigenetics and Environmental Factorsmentioning
confidence: 99%
“…In the mammalian lifecycle, the most pronounced epigenetic remodeling occurs during two distinct developmental stages, where the acquired epigenetic information has to be erased and reset [16][17][18]. Widespread loss of DNA methylation has been observed in the zygotes immediately following fertilization [42] and again during maturation of the primordial germ cells (PGCs), the progenitors of sperm and oocytes (Fig. 1B) [43].…”
Section: The Epigenetic Memory: Biological Functions Of Dna Methylationmentioning
confidence: 99%